(untitled) (International Journal of Engineering and Computer Science, 2017)
With the increase in smart phone users and communication through messaging. In all smart phones there are various applications (apps) which can be used for communication with each other. But many of these apps are sending text data in plain text format through network. When using such apps in a public Wi-Fi network, anybody can able to sniff incoming and outgoing messages. Data compression is a common requirement for most of the computerized applications. There are number of data compression algorithms, which are dedicated to compress different data formats. Even for a single data type there are number of different compression algorithms, which use different approaches. Mobile communication devices have become popular tools for gathering and disseminating information and data. This paper proposes an efficient data compression technique by doing some modification to Huffman Coding. The aim of this paper is to compress data to send through Android based mobiles to optimize bandwidth.